Twenty-Four–Hour Voiding Diaries Versus 3-Day Voiding Diaries: A Clinical Comparison. Issue 6 (November 2017) - Elmer, Caroline; Murphy, Amber; Elliott, John O.; Book, Nicole M.
Abstract : Objective: This study aimed to determine if 24-hour versus 3-day voiding diary affects medical decision making for women with urinary incontinence. Methods: A retrospective chart review was conducted of patients presenting to the OhioHealth Urogynecology Physician group for urinary incontinence from 2009 to 2011. Practice protocol includes patient completion of a 3-day voiding diary before their appointment. Diagnostic and treatment plans were extracted based on the initial patient encounter and 3-day voiding diary. A chart review was then completed with the first 24 hours of the same diaries, principal history, and physical examination data compiled into a separate chart. These charts were then reevaluated by the same physician who initially provided care to the patient but were blinded to their previous orders, impressions, and plans. New plans were then created based on the 24-hour diaries and compared with the original plans. Results: One hundred eighty-six charts were reviewed. There was good agreement between 24-hour and 3-day diaries in recommendations for first-line behavioral modifications (Κ > 0.6) and moderate agreement between diaries in initiation of medical therapy or trial of incontinence pessary (Κ > 0.4). However, 24-hour diaries resulted in a statistically significant increase in invasive diagnostic tests ( P < 0.019) and other treatment recommendations when compared with 3-day diaries. Conclusions: Use of 24-hour diaries may result in increased testing when compared with 3-day diaries. It may be prudent to postpone invasive testing in those patients who initially are noncompliant with a longer diary until a more complete history can be obtained. Abstract : Results of our study suggest the trend of increasingly truncated bladder diaries may result in increased invasive testing and other treatment recommendations.